Providing a Framework for the Implementation, Development, and Assessment of Financial Literacy Among Students (Case Study: Technical and Vocational University) - Ghaderi Rahaghi, Majid; Alamdari, Saber Khandan (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: The aim of this study is to present a framework for the implementation, development, and assessment of financial literacy among students at the Technical and Vocational University. Methodology: The research method employed in this study is a descriptive-survey approach. After extracting and validating the appropriate questionnaire, it was distributed among the students. The statistical population of this section of the research comprised associate and bachelor’s degree students. Findings: The findings indicate that the three dimensions of financial literacy (financial knowledge, financial behavior, financial attitude) among students are influenced by their field of study (0.236) and their parents’ occupation (0.205). The results suggest that with higher levels of financial literacy in the three dimensions among students, their field of study is relatively less significant, and with higher levels of financial literacy, the significance of their parents’ occupation also diminishes. Conclusion: The proposed model assists managers and decision-makers in identifying the outcomes of implementing this approach and in adopting measures to improve the methods that enhance the quality of education.